RETRACTED: Synthesis of vinyl esters of some furan carboxylic acids based on vinyl acetate - Parmanov A.B.; Nurmanov S.E.; Abdullaev J.U.; Mamajonov J.Sh.; Abdurakhmanova S.S.; Boykobilov D.B.; Todjiev J.N.; Juraboev F.M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001